PoseIDON: 6DoF pose estimation with foundation model features for marine sediment burial mapping - Jerry Yan; Chinmay Talegaonkar; Nicholas Antipa; Eric Terrill; Sophia Merrifield (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Smart farming with AI: Enhancing anemia detection in small ruminants - Aftab Siddique; Sophia Khan; Thomas H. Terrill; Ajit K. Mahaptra; Sudhanshu S. Panda; Eric R. Morgan; Andres A. Pech-Cervantes; Reginald Randall; Anurag Singh; Phaneendra Batchu; Priyanka Gurrapu; Jan A. van Wyk (Veterinary Parasitology, 2025)

PyPlume: A toolkit for rapid ocean surface transport assessments - Jerry Yan; Thomas Cook; Allison Ho; Mark Otero; Peter A. Rogowski; Mika Siegelman; Eric Terrill; Sophia Merrifield (Environmental Modelling & Software, 2023)

An early warning system for wave-driven coastal flooding at Imperial Beach, CA - Mark A. Merrifield; Mele Johnson; R. T. Guza; Julia W. Fiedler; Adam P. Young; Cassandra S. Henderson; Athina M. Z. Lange; William C. O’Reilly; Bonnie C. Ludka; Michele Okihiro; Timu Gallien; Kyle Pappas; et al. (Natural Hazards, 2021)
Waves overtop berms and seawalls along the shoreline of Imperial Beach (IB), CA when energetic winter swell and high tide coincide. These intermittent, few-hour long events flood low-lying areas and pose a growing inundation risk as sea levels rise. To support city flood response and management, an IB flood warning system was developed. Total water level (TWL) forecasts combine predictions of tides and sea-level anomalies with wave runup estimates based on incident wave forecasts and the nonlinear wave model SWASH. In contrast to widely used empirical runup formulas that rely on significant wave height and peak period, and use only a foreshore slope for bathymetry, the SWASH model incorporates spectral incident wave forcing and uses the cross-shore depth profile. TWL forecasts using a SWASH emulator demonstrate skill several days in advance. Observations set TWL thresholds for minor and moderate flooding. The specific wave and water level conditions that lead to flooding, and key contributors to TWL uncertainty, are identified. TWL forecast skill is reduced by errors in the incident wave forecast and the one-dimensional runup model, and lack of information of variable beach morphology (e.g., protective sand berms can erode during storms). Model errors are largest for the most extreme events. Without mitigation, projected sea-level rise will substantially increase the duration and severity of street flooding. Application of the warning system approach to other locations requires incident wave hindcasts and forecasts, numerical simulation of the runup associated with local storms and beach morphology, and model calibration with flood observations.

Performance Assessments of Hurricane Wave Hindcasts - Peter Rogowski; Sophia Merrifield; Clarence Collins; Tyler Hesser; Allison Ho; Randy Bucciarelli; James Behrens; Eric Terrill (Journal of Marine Science and Engineering, 2021)
Landfalling tropical cyclones (TC) generate extreme waves, introducing significant property, personal, and financial risks and damage. Accurate simulations of the sea state during these storms are used to support risk and damage assessments and the design of coastal structures. However, the TCs generate a complex surface gravity wave field as a result of the inherently strong temporal and spatial gradients of the wind forcing. This complexity is a significant challenge to model. To advance our understanding of the performance of these models on the eastern seaboard of the United States, we conduct an assessment of four hindcast products, three based on WAVEWATCH-III and the other using the Wave Modeling project, for six major landfall TCs between 2011–2019. Unique to our assessment was a comprehensive analysis of these hindcast products against an array of fixed wave buoys that generate high quality data. The analysis reveals a general tendency for the wave models to underestimate significant wave height (Hs) around the peak of the TC. However, when viewed on an individual TC basis, distinct Hs error patterns are evident. Case studies of hurricanes Sandy and Florence illustrate complex Hs bias patterns, likely resulting from various mechanisms including insufficient resolution, improper wind input and source term parameterization (e.g., drag coefficient), and omission of wave–current interactions. Despite the added challenges of simulating complex wave fields in shallow coastal waters, the higher resolution Wave Information Study and National Centers for Environmental Prediction (ST4 parameterization only) hindcasts perform relatively well. Results from this study illustrate the challenge of simulating the spatial and temporal variability of TC generated wave fields and demonstrate the value of in-situ validation data such as the north Atlantic buoy array.

Ngaraard Pinnacle, Palau: An Undersea “Island” in the Flow - Patrick Colin; Shaun Johnston; Jennifer MacKinnon; Celia Ou; Daniel Rudnick; Eric Terrill; Steven Lindfield; Heidi Batchelor (Oceanography, 2019)

Tropical Western Pacific Thermal Structure and its Relationship to Ocean Surface Variables: A Numerical State Estimate and Forereef Temperature Records - Travis Schramek; Bruce Cornuelle; Ganesh Gopalakrishnan; Patrick Colin; Sonia Rowley; Mark Merrifield; Eric Terrill (Oceanography, 2019)

Energy and Momentum Lost to Wake Eddies and Lee Waves Generated by the North Equatorial Current and Tidal Flows at Peleliu, Palau - Shaun Johnston; Jennifer MacKinnon; Patrick Colin; Patrick Haley; Pierre Lermusiaux; Andrew Lucas; Mark Merrifield; Sophia Merrifield; Chris Mirabito; Jonathan Nash; Celia Ou; Mika Siegelman; et al. (Oceanography, 2019)

Island Wakes Observed from High-Frequency Current Mapping Radar - Sophia Merrifield; Patrick Colin; Thomas Cook; Carlos Garcia-Moreno; Jennifer MacKinnon; Mark Otero; Travis Schramek; Mika Siegelman; Harper Simmons; Eric Terrill (Oceanography, 2019)

Observations of Near-Inertial Surface Currents at Palau - Mika Siegelman; Mark Merrifield; Eric Firing; Jennifer MacKinnon; Matthew Alford; Gunnar Voet; Hemantha Wijesekera; Travis Schramek; Kristin Zeiden; Eric Terrill (Oceanography, 2019)

Typhoon-Forced Waves Around a Western Pacific Island Nation - Sophia Merrifield; Travis Schramek; Sean Celona; Ana Beatriz Villas Bôas; Patrick Colin; Eric Terrill (Oceanography, 2019)

Eddies, Topography, and the Abyssal Flow by the Kyushu-Palau Ridge Near Velasco Reef - Magdalena Andres; Mika Siegelman; Verena Hormann; Ruth Musgrave; Sophia Merrifield; Daniel Rudnick; Mark Merrifield; Matthew Alford; Gunnar Voet; Hemantha Wijesekera; Jennifer MacKinnon; Luca Centurioni; et al. (Oceanography, 2019)

FLEAT: A Multiscale Observational and Modeling Program to Understand How Topography Affects Flows in the Western North Pacific - Shaun Johnston; Martha Schönau; Terri Paluszkiewicz; Jennifer MacKinnon; Brian Arbic; Patrick Colin; Matthew Alford; Magdalena Andres; Luca Centurioni; Hans Graber; Karl Helfrich; Verena Hormann; et al. (Oceanography, 2019)

Mapping Fish Chorus Distributions in Southern California Using an Autonomous Wave Glider - Camille M. L. S. Pagniello; Megan A. Cimino; Eric Terrill (Frontiers in Marine Science, 2019)

Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Ana B. Villas Bôas; Fabrice Ardhuin; Alex Ayet; Mark A. Bourassa; Peter Brandt; Betrand Chapron; Bruce D. Cornuelle; J. T. Farrar; Melanie R. Fewings; Baylor Fox-Kemper; Sarah T. Gille; Christine Gommenginger; et al. (Frontiers in Marine Science, 2019)

Air-Sea-Land Forcing in the Gulf of Tonkin: Assessing Seasonal Variability Using Modern Tools - Peter Rogowski; Javier Zavala-Garay; Kipp Shearman; Eric Terrill; John Wilkin; Tran Hong Lam (Oceanography, 2019)

The Global High Frequency Radar Network - Hugh Roarty; Thomas Cook; Lisa Hazard; Doug George; Jack Harlan; Simone Cosoli; Lucy Wyatt; Enrique Alvarez Fanjul; Eric Terrill; Mark Otero; John Largier; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

Northern Arabian Sea Circulation-Autonomous Research (NASCar): A Research Initiative Based on Autonomous Sensors - Luca Centurioni; Verena Hormann; Lynne Talley; Isabella Arzeno; Lisa Beal; Michael Caruso; Patrick Conry; Rosalind Echols; Harindra Fernando; Sarah Giddings; Arnold Gordon; Hans Graber; et al. (Oceanography, 2017)

Project Recover: Extending the Applications of Unmanned Platforms and Autonomy to Support Underwater MIA Searches - Eric Terrill; Mark Moline; Patrick Scannon; Eric Gallimore; Travis Shramek; Andy Nager; Robert Hess; Megan Cimino; Patrick Colin; Andrew Pietruszka; Mark Anderson (Oceanography, 2017)

Navy Nearshore Ocean Prediction Systems - Jayaram Veeramony; Mark Orzech; Kacey Edwards; Michael Gilligan; Jeikook Choi; Eric Terrill; Tony De Paolo (Oceanography, 2014)

Marine radar ocean wave retrieval’s dependency on range and azimuth - Björn Lund; Clarence O. Collins; Hans C. Graber; Eric Terrill; Thomas H. C. Herbers (Ocean Dynamics, 2014)

Tiny Bubbles: An Overlooked Optical Constituent - Eric Terrill; Marlon Lewis (Oceanography, 2004)